1998
DOI: 10.1111/j.1558-5646.1998.tb03695.x
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL EVOLUTION OF RESISTANCE IN BRASSICA RAPA : CORRELATED RESPONSE OF TOLERANCE IN LINES SELECTED FOR GLUCOSINOLATE CONTENT

Abstract: The evolutionary response of plant populations to selection for increased defense may be constrained by costs of defense. The purpose of this study was to investigate such constraints on the evolution of defense due to a cost of defense manifested as a trade-off between defense and tolerance. Variation in the response to artificial damage (tolerance) among lines of Brassica rapa that had been artificially selected for foliar glucosinolate content (defense) was examined. Leaf area was removed from replicates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
108
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 44 publications
5
108
1
Order By: Relevance
“…studies reported a negative relationship between tolerance and resistance to herbivory (Fineblum & Rausher, 1995;Stowe, 1998;Baucom & Mauricio, 2008) and RĂ„berg et al (2007) presented a similar finding in mice infected with malaria. Other studies reported no correlation between tolerance and resistance in plants subjected to herbivores (Mauricio et al, 1997), in humans infected with HIV (Regoes et al, 2014) or in wild sheep infected with a parasite (Maze-Guilmo et al, 2014).…”
Section: Introductionsupporting
confidence: 61%
“…studies reported a negative relationship between tolerance and resistance to herbivory (Fineblum & Rausher, 1995;Stowe, 1998;Baucom & Mauricio, 2008) and RĂ„berg et al (2007) presented a similar finding in mice infected with malaria. Other studies reported no correlation between tolerance and resistance in plants subjected to herbivores (Mauricio et al, 1997), in humans infected with HIV (Regoes et al, 2014) or in wild sheep infected with a parasite (Maze-Guilmo et al, 2014).…”
Section: Introductionsupporting
confidence: 61%
“…Genetic variation for tolerance could also be maintained by a cost (Simms and Triplett, 1994;Mauricio et al, 1997). Theoretical considerations of herbivory and disease suggest that selection may generate trade-offs between tolerance and resistance (van der Meijden et al, 1988;Simms and Triplett, 1994;Rausher, 1995, 2002;Stowe, 1998;Strauss and Agrawal, 1999;Tiffin, 2000; but see Restif and Koella, 2004). As resistant genotypes should experience less damage, selection for the ability of these genotypes to tolerate damage would likely be weak.…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance, defined as the ability of a plant to incur herbivore damage without a corresponding reduction in fitness, may result in very different evolutionary and ecological dynamics between plants and herbivores than plant resistance (van der Meijden et al 1988;Fineblum and Rausher 1995;Tiffin 2000). Thus, understanding tolerance is necessary to understand plant-herbivore interactions (reviewed in Rosenthal and Kotenan 1994;Strauss and Agrawal 1999).Recent studies on tolerance have focused on environmental conditions that affect the expression of tolerance (Mashinski and Whitham 1989;Hjalten et al 1993;Fay et al 1996;Juenger and Bergelson 1997); mechanisms of tolerance (reviewed in Strauss and Agrawal 1999), the presence of costs, including trade-offs with resistance and trade-offs with fitness in the absence of herbivores (Fineblum and Rausher 1995;Mauricio et al 1997;Stowe 1998;Tiffin and Rausher 1999); and the pattern of selection acting on tolerance (Mauricio et al 1997;Tiffin and Rausher 1999). In these studies, researchers have employed naturally occurring (Paige and Whitham 1987; van der Meijden et al 1988;Mashinski and Whitham 1989;Mauricio et al 1997;Tiffin and Rausher 1999) …”
mentioning
confidence: 99%
“…In these studies, researchers have employed naturally occurring (Paige and Whitham 1987;van der Meijden et al 1988;Mashinski and Whitham 1989;Mauricio et al 1997;Tiffin and Rausher 1999) as well as artificial or manipulated (imposed) herbivory (Mashinski and Whitham 1989;Doak 1991;Hjalten et al 1993;Fineblum and Rausher 1995;Rosenthal and Welter 1995;Fay et al 1996;Juenger and Bergelson 1997;Lennartsson et al 1997;Stowe 1998;Agrawal et al 1999) to estimate values of tolerance. However, the majority of studies have relied on imposed herbivory , presumably because of an implicit assumption that naturally occurring herbivore damage will result in poor estimates of tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation